The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/app12189325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Detect COVID-19: Enhanced Deep Learning Models with Convolutional Neural Networks

Abstract: The novel coronavirus (COVID-19) is a contagious viral disease that has rapidly spread worldwide since December 2019, causing the disruption of life and heavy economic losses. Since the beginning of the virus outbreak, a polymerase chain reaction has been used to detect the virus. However, since it is an expensive and slow method, artificial intelligence researchers have attempted to develop quick, inexpensive alternative methods of diagnosis to help doctors identify positive cases. Therefore, researchers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Ramadhan et al [13] built a VGG16-CNN to classify three public datasets that consist of chest X-ray images of COVID-19 patients. Binary classification was conducted on three datasets, and the model achieved 97% accuracy on the first dataset, 98.73% on the second dataset, and the highest accuracy was achieved using the third dataset, i.e., 99.76%.…”
Section: Covid-19mentioning
confidence: 99%
“…Ramadhan et al [13] built a VGG16-CNN to classify three public datasets that consist of chest X-ray images of COVID-19 patients. Binary classification was conducted on three datasets, and the model achieved 97% accuracy on the first dataset, 98.73% on the second dataset, and the highest accuracy was achieved using the third dataset, i.e., 99.76%.…”
Section: Covid-19mentioning
confidence: 99%
“…The architecture is widely used in computer vision applications such as object detection and image segmentation (Popescu et al, 2022). The architecture for VGG-16 (Ramadhan & Baykara, 2022) is shown in Figure 4A, and it was the most used for insect detection and classification tasks. The convolutional layers are responsible for extracting features from the input image, while the pooling layers reduce the spatial dimensions of the feature maps to reduce computation time.…”
Section: Neural Network Used In Insect Detection Segmentation and Cla...mentioning
confidence: 99%
“…The researchers collected CXR images from various sources (from different classes of chests humans) to detect COVID-19 disease. On the other hand, the study [27] used a pre-trained approach called VGG16-CNN to detect COVID-19 cases using CXR images. While the study achieved an accuracy of 97.50% for multiple classifications, the authors tested the models and found varying proportions, such as an F1-score rate, precision rate, recall rate, and overall accuracy.…”
Section: Related Workmentioning
confidence: 99%